Targeting Adult Neurogenesis for Poststroke Therapy. (20th July 2017) - Lu, Jianfei; Manaenko, Anatol; Hu, Qin
Abstract : Adult neurogenesis mainly occurs at the subventricular zone (SVZ) on the walls of the lateral ventricle and the subgranular zone (SGZ) of the dentate gyrus (DG). However, the majority of newborn neurons undergo programmed cell death (PCD) during the period of proliferation, migration, and integration. Stroke activates neural stem cells (NSCs) in both SVZ and SGZ. This process is regulated by a wide variety of signaling pathways. However, the newborn neurons derived from adult neurogenesis are insufficient for tissue repair and function recovery. Thus, enhancing the endogenous neurogenesis driven by ischemia and promoting the survival of newborn neurons can be promising therapeutic interventions for stroke. Here, we present an overview of the process of adult neurogenesis and the potential of stroke-induced neurogenesis on brain repair.